Context-dependent effects of parental effort on malaria infection in a wild bird population, and their role in reproductive trade-offs. - Knowles, S; Wood, M; Sheldon, B (2010)
Although trade-offs between reproductive effort and other fitness components are frequently documented in wild populations, the underlying physiological mechanisms remain poorly understood. Parasitism has been suggested to mediate reproductive trade-offs, yet only a limited number of parasite taxa have been studied, and reproductive effort-induced changes in parasitism are rarely linked to trade-offs observed in the same population. We conducted a brood size manipulation experiment in blue tits (Cyanistes caeruleus) infected with malaria (Plasmodium) parasites, and used quantitative PCR to measure changes in parasitaemia. In one of two years investigated, parasitaemia increased as a result of brood enlargement, and was also positively associated with two other indicators of reproductive effort: clutch size and single parenthood. These associations between both experimental and naturally varying reproductive effort and parasitaemia suggest that immune control of chronic malaria infections can be compromised when parents are working hard. Brood size manipulation significantly affected the number of independent offspring produced, which was maximised when brood size was unchanged. Moreover, when parents were infected with one of two common Plasmodium species, the shape of this trade-off curve was more pronounced, suggesting that parasitic infection may exacerbate the trade-off between quantity and quality of offspring. Although the involvement of parasites in survival costs of reproduction has received much attention, these results suggest their role in other commonly documented reproductive trade-offs, such as that between number and quality of offspring, warrants further study.